Aprendizaje colaborativo vs. aprendizaje cooperativo: una experiencia dentro del contexto de la programación de computadores en ingeniería de sistemas usando problem based learning (2017)
This article is one of the products of a research project in the classroom. The purpose was to compare, from the experimental, two approaches of group work with the aim of having solid elements of judgment. This would allow inferring the convenience of one of these methods, within the teaching and learning process of computer programming, in an initial course of systems engineering. For that purpose, an experimental design in the classroom during the development of the subject programming over six semesters was drawn, with the establishment of parallel observation subgroups within the same course. Indeed, the research in engineering programs is not only convenient but very necessary for teachers to have consistent criteria at the time of searching ways for their students to achieve learning objectives. As a conclusion, if they take advantage of the appropriate form, the approaches to collaborative learning and cooperative learning are pathways that allow interaction, communication, improvement, cohesion, autonomy, and socialization; highly necessary characteristics that the engineer of our times can encourage their training process as a student.